KARAKTERISTIK HUBUNGAN HUKUM DALAM ASURANSI JASARAHARJA TERHADAP KLAIM KORBAN KECELAKAAN ANGKUTAN UMUM - Hilda Yunita Sabrie; Rizky Amalia (Yuridika, 2015)
The average person in Indonesia uses public transport in daily life. If observed in Indonesia has many diverse public transport both provided by the government and in cooperation with private parties. Neglected condition of public transportation sometimes is the main factor why traffic accident happens to public transportation. This causes many accident on land, water, even air public transportation, which in this case citizens are the victim. Government has laid out policy by providing PT Asuransi Jasaraharja as compulsory social insurance which is supposed to give compensation for public transportation’s victim in certain circumstances. However, not every citizens know their rights regarding the compensation given by PT Asuransi Jasarahardja when the traffic accident happens. Compensation has to go through particular procedure made by PT Asuransi Jasaraharja. Because if they dont, then the compensation cannot be given.In the insurance of premium services the collection is not based on the agreement between the two parties but has been regulated in the law. This is what distinguishes between the insurance of raharja services as compulsory social insurance with other insurance.